2002
DOI: 10.1590/s0100-879x2002000800007
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure of term newborns during the first week of life

Abstract: The progressive behavior of the blood pressure of term newborns during the first week of life was assessed by the simultaneous use of oscillometric and Doppler methods. A total of 174 term neonates born at the Municipal Hospital Odilon Behrens in Belo Horizonte, from March 1996 to February 1997, were prospectively assessed. The oscillometric and Doppler ultrasonic methods were simultaneously used for four consecutive recordings obtained at 12 ± 6, 24 ± 6 and 72 ± 24 h and on the 7th ± 1 day of life. The combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Though this was a weak relationship, a similar finding was reported by [17]. Contrastingly, Nascimento in Brazil found no relationship between birth length and systolic blood pressure [16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Though this was a weak relationship, a similar finding was reported by [17]. Contrastingly, Nascimento in Brazil found no relationship between birth length and systolic blood pressure [16].…”
Section: Discussionsupporting
confidence: 80%
“…Most studies carried out worldwide including Nigeria agreed that neonatal weight is a major determinant of neonatal systolic blood pressure [13]- [15]. The role of other physical factors, especially length has been inconsistently reported [16], [17]. Data about the effects of social factors on early neonatal blood pressure are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Although the blood pressure (BP) was recorded every 60 s (since the cuff cannot be inflated and deflated every 5 s), the GE DASH 4000 monitor repeats the same BP value for the next 60 s. A highly significant correlation has been observed between the neonatal BP measured simultaneously by the oscillometric and Doppler ultrasonic methods 40. A variation in BP during the 60 s interval required is unlikely; therefore, the parameters recorded every 5 s were matched with BP data.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that the blood pressure of premature infants is lower than that of term infants at birth; [37][38][39][40] however, blood pressure increased steadily in the first week of life. 41 Therefore, the infants with low blood pressure were younger and had immature physiological functions; hence, the possibility of requiring mechanical ventilation increases.…”
Section: Discussionmentioning
confidence: 99%